1985
DOI: 10.1002/fam.810090203
|View full text |Cite
|
Sign up to set email alerts
|

Some factors influencing fire spread over room linings and in the ASTM E–84 tunnel test

Abstract: An examination of the correlative relationship between room fire intensity (temperature) and flammability data for materials, ASTM E-84 flame ratings and energy release rate from calorimetry devices is presented for fire spread on linings. The results of the analysis show the significance of two modes of flame spread-wind-aided and opposed-flow spread. The factors important in these spread modes are considered from approximate solutions developed for turbulent flow. As the importance of energy release rate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Because the ignition time of the polyisocyanurate foam is very short, the model predicts that flames spread quickly to the end of the tunnel. The anomalous behavior of exposed plastic foam materials in the Steiner tunnel test is well known [2]. Figure 10 shows that the predicted SDI classification is consistent with that based on the measurements except for the glassfiber reinforced plastic.…”
Section: Ignition Time Predictionssupporting
confidence: 72%
See 1 more Smart Citation
“…Because the ignition time of the polyisocyanurate foam is very short, the model predicts that flames spread quickly to the end of the tunnel. The anomalous behavior of exposed plastic foam materials in the Steiner tunnel test is well known [2]. Figure 10 shows that the predicted SDI classification is consistent with that based on the measurements except for the glassfiber reinforced plastic.…”
Section: Ignition Time Predictionssupporting
confidence: 72%
“…The test is not suitable for quality control for the same reason. To address this problem, a number of correlations and models have been developed to predict Steiner tunnel test performance on the basis of data from a small-scale test such as the cone calorimeter [1][2][3][4][5][6][7][8][9][10]. Most of these predictive methods have significant limitations because they were developed for specific types of products.…”
Section: Introductionmentioning
confidence: 99%
“…While it has been demonstrated that the Tunnel test results do not correlate (rank) foamed plastics in a consistent manner when compared to full scale room fire results [3], the Tunnel test results are still used to approve foamed plastics. The de facto position taken with respect to foamed plastics is that the Tunnel test results can be compared to one another for the purposes of obtaining a relative combustibility ranking.…”
Section: Metal Edge Framementioning
confidence: 99%
“…The motivations for replacing the Tunnel test include the lack of correlation of the test results to known fire performance of exposed foamed plastics in large scale tests, the variability of Tunnel ratings for repeat tests of the same material, and the thickness limitations of the Tunnel test. The lack of correlation between the Tunnel test results and large scale tests, such as room fire tests [3] or the Factory Mutual 25 ft. comer test [4], raises questions about the applicability of the Tunnel test for foamed plastics. The variability of Tunnel test results of the same material is a concern since in some instances, a material may pass and fail repeated tests.…”
Section: Metal Edge Framementioning
confidence: 99%
See 1 more Smart Citation